Way Up High in a Tall Green Tree - Peck, Jan; Petrone, Valeria (New York : Simon & Schuster Books for Young Readers, 2005)
A girl climbs a tree in the rainforest saying goodnight to all the creatures, but it is really her bunkbed as she settles down with all her stuffed animals.